2012
DOI: 10.1016/j.aop.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ion-acoustic structures in a nonextensive electron–positron–ion–dust plasma: Modulational instability and rogue waves

Abstract: a b s t r a c tThe nonlinear propagation of planar and nonplanar (cylindrical and spherical) ion-acoustic waves in an unmagnetized electron-positron-ion-dust plasma with two-electron temperature distributions is investigated in the context of the nonextensive statistics. Using the reductive perturbation method, a modified nonlinear Schrödinger equation is derived for the potential wave amplitude. The effects of plasma parameters on the modulational instability of ion-acoustic waves are discussed in detail for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Also, they found that the super rogue waves w 2 may be more real than the first one (w 1 Þ in fields concerned with nonlinear dispersive media, e.g., in optics, plasma physics, and superfluidity. Furthermore, Guo et al 45 studied the nonlinear propagation of planar ion-acoustic rogue waves (IARWs) in an unmagnetized electron-positron-ion dust plasma. They investigated the influence of the plasma parameters on the nonlinear structures of the first-and second-order IARW solutions within the modulational unstability region.…”
Section: Rational Solutions Of the Nlsementioning
confidence: 99%
“…Also, they found that the super rogue waves w 2 may be more real than the first one (w 1 Þ in fields concerned with nonlinear dispersive media, e.g., in optics, plasma physics, and superfluidity. Furthermore, Guo et al 45 studied the nonlinear propagation of planar ion-acoustic rogue waves (IARWs) in an unmagnetized electron-positron-ion dust plasma. They investigated the influence of the plasma parameters on the nonlinear structures of the first-and second-order IARW solutions within the modulational unstability region.…”
Section: Rational Solutions Of the Nlsementioning
confidence: 99%
“…A large amount of attention has been devoted in various areas to study this freak wave which appear in superfluid helium, Bose-Einstein condensates, ocean, 17 and plasma physics. [18][19][20][21] Tribeche et al 22 made an attempt to study the characteristics of ion-acoustic (IA) solitons in the frame work of Tsallis distribution. Bains et al 23 extended the same work and studied the modulational instability of IA solitons.…”
mentioning
confidence: 99%
“…To study the MI of DAWs, we will derive the NLSE by employing the standard multiple scale (reductive perturbation) technique . Let A be the state (column) vector ( n d , u d , ϕ ) T , describing the system's state at a given position x and instant t. We shall consider small deviations from the equilibrium state A (0) = (1, 0, 0) T by taking …”
Section: Derivation Of Nlsementioning
confidence: 99%